Biological Effect of Peronema canescens Jack on The Surface Changes of Alginate Mold - Fadriyanti, Okmes; Afriza, Dhona; Chaerunnisa, Chaerunnisa (Dentistry Faculty, 2023)
Background. The patients oral cavity is one of the transmission agents that has the potential for cross-infection. Saliva adhering to the surface of the alginate mold, apart from containing a lot of microorganisms, also disrupts changes in the alginate surface due to changes in salivary pH. Sungkai leaves (Peronema canescens Jack) contain active compounds that can maintain the alginate constituent elements integrity and alginates surface properties. Objective. This study aimed to determine the biological properties of Peronema canescens Jack on changes in the alginate impression surface by immersion and spraying methods. Materials and Methods. The research material comprised 72 alginate impressions totaling six groups (12 samples/group). The sample categories used matrices and stainless steel rings and were measured within 5, 10, and 15 minutes. Changes in the alginate impression surface were observed using a stereo microscope. Results. Soaking and spraying with Sungkai leaf extract within 5 and 10 minutes did not affect the surface of the mold, while spraying within 15 minutes was within standard clinical limits. Conclusion. Sungkai leaf extract can maintain the integrity of alginate impressions by immersion and spraying techniques.